A new fuzzy Lyapunov approach to non-quadratic stabilization of Takagi-Sugeno fuzzy models - Abdelmalek, Ibtissem; Goléa, Noureddine; Hadjili, Mohamed Laid (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, new non-quadratic stability conditions are derived based on the parallel distributed compensation scheme to stabilize Takagi-Sugeno (T-S) fuzzy systems. We use a non-quadratic Lyapunov function as a fuzzy mixture of multiple quadratic Lyapunov functions. The quadratic Lyapunov functions share the same membership functions with the T-S fuzzy model.
Keywords: T-S fuzzy systems; non-quadratic stability conditions; linear matrix inequalities; parallel distributed compensation; stabilization